Optical coherence tomography: a reliable alternative to invasive histological assessment of acute wound healing in human skin?. (1st April 2014) - Greaves, N.S.; Benatar, B.; Whiteside, S.; Alonso‐Rasgado, T.; Baguneid, M.; Bayat, A.
Summary: Background: Gold‐standard assessment of acute wound healing has traditionally been through histological analysis of biopsied tissue. However, this process is invasive with recognized side‐effects. Optical coherence tomography (OCT) is a noninvasive technique generating high‐resolution real‐time images of cutaneous architecture. Objectives: To compare OCT with histological assessment of in vivo acute wound healing and ascertain the level of agreement between modalities for measurement of defined cutaneous structures. Methods: Punch biopsies (5 mm) were harvested from 50 healthy volunteers. Wounds healed by secondary intention until they were re‐excised 7, 14, 21 or 28 days later depending on random group allocation. Wounds were assessed weekly for 6 weeks using OCT and compared with histological findings derived from time‐matched biopsies. Dimensions of four cutaneous structures were measured using both modalities and the level of agreement was established by Bland–Altman analysis. The mean greyscale value (MGV) of the upper reticular dermis was derived from OCT images at all time points. Results: Both techniques showed anatomical congruity in normal and wounded skin with correlating architectural changes associated with inflammatory, proliferative and remodelling wound healing phases. MGV was significantly increased 6 weeks after wounding ( P = 0·001) and may represent a novel measure of wound fibrosis. Despite good association of histomorphometric values with low but consistent bias (range −4·181 to 0·431 μm), Bland–Altman plots demonstrated poor agreement between OCT and histology. Conclusions: Optical coherence tomography enabled accurate assessment of healing tissue comparable with histological analysis of biopsy specimens. This noninvasive tool is highly suited to wound assessment and may represent a diagnostic alternative to punch biopsies.